Completely geodetic families of space curves order three - Petruškevičiūtė, D. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Д. Петрушкевичуте. Вполне геодезические семейства пространственных кривых порядка D. Petruškevičiūtė. Trečios eilės erdvinių kreivių pilnai geodezinės šeimos